THE EFFECTIVENESS OF USING HIKAYAT PRANG SABI IN PjBL APPROACH TO IMPROVE STUDENTS' CRITICAL THINKING - Rizki Dhian Nushur; Diyana Dewie Astutie (English Education Department, 2019)
Various types of methods, strategies, and learning approaches are developed because the development of the era occurs very quickly and rapidly. At this time, education provided to students must train them to be able to deal with various problems in real life.To support and assist students in this case, project based learning or PjBL is formed to be applied as a learning approach. This study aims to know the effectiveness of using Hikayat Prang Sabi in PjBL approach to improve students' critical thinking. The study was conducted in STKIP BumiPersadaLhokseumawe with several students who randomly selected as the objects of this research. Through this approach, the learning process will be carried out in a team where the students are required to be able to take steps that consist of Determination of basic questions (essential), Designing project planning, compile a schedule, monitor project progress, testing learning processes and results, evaluating the experience of making a project or experience of learning activities.This research is a kind of qualitative research which is in collected the data used interview, FGD, and document review. In analyzing the data, it uses the style of Miles &Hubermen method.